FAKTOR YANG MEMPENGARUHI PEMBIAYAAN BERMASALAH GOLONGAN BERPENGHASILAN TETAP - Kanda, Pajri; Saiful, Saiful; Puspita, Lisa Martiah Nila (UNIB Press, 2016)
The aim of this reaserch is to analyze the the influencing of fraud, poor management, internal problem between debtor and the company, Bad debtor attitude, abuse installments by coordinator on financing performance problems of fix income group debtors of Islamic bank.By using cluster sampling method, the 100 respondents were selected as a sample of the study. Using logistic regression analysis, this study found that fraud and debtor attitude influence on financing performance of fix income debtors. It mean that both fraud and debtor attitude can used to predict the non performing financing of fix income debtors in Islamic Bank. This study also found that poor management, internal problem between debtor anda the company and abuse installments by coordinator are not influence on financing performance problems of fix income group debtors.